KONSUMSI OBAT TRADISIONAL MADURA SEBAGAI ALTERNATIF PREVENSI DINI DISTRIBUSI COVID-19 - Syaifiyatul H. (BORNEO JOURNAL OF PHARMASCIENTECH, 2020)
Corona Virus Disease-2019 (COVID-19) is an infectious disease caused by the Coronavirus class of Coronaviridae which infects epithelial cells in the respiratory tract. Effects in the form of fever, cough to shortness of breath. But some without symptoms also have the potential to pass it on to other people. COVID-19 can be anticipated with good immunity by consuming the Madura OT herb. Therefore, Madurese traditional medicine which is believed to be able to increase immunity needs to be observed. The research objective was to determine the consumption of Madurese traditional medicine as an alternative to early prevention of the distribution of COVID-19 in Madura. Observational study method - qualitative descriptive January - March 2020 in 4 Madura districts: Bangkalan, Sampang, Pamekasan, and Sumenep. A sample of 200 Madurese traditional medicine consumers. The results of the data show that the Madurese traditional medicine ingredients contain the highest ingredients of ginger, turmeric and betel leaf consumed by the Sumenep community and the lowest is the Bangkalan Community. The satisfaction level of the Madurese community after consuming the Madurese traditional medicine herb shows satisfaction. The conclusion is that the type of Madurese traditional medicine consumed is believed to be able to suppress the growth of the corona virus in the body, including: ginger, turmeric, betel leaf; The Madurese community expressed “satisfaction” after consuming Madurese traditional medicine during the COVID-19 pandemic situation; Availability of basic ingredients of Madurese traditional medicine concoctions available in abundance in traditional markets; The price of basic materials for Madurese traditional medicine increases from February to March 2020.